Religion and Politics in The Framework of Secularism: A Philosophical Dialogue Between Charles Taylor and Syed M. Naquib Al-Attas - Iman, Hafidz (Universitas Islam Indonesia, 2025)
This study aims to analyze the relationship between religion and politics through a comparative examination of the thoughts of Charles Taylor and Syed Muhammad Naquib al-Attas in their respective responses to secularism. Employing a qualitative method and a library research approach, the study draws on the primary works of both thinkers as well as relevant academic references. This study is motivated by the absence of a deep philosophical dialogue between Western political philosophy and Islamic thought in redefining the ethical foundations of the modern pluralistic state. This article argues that Taylor’s approach is relevant for promoting equality in pluralistic societies such as Indonesia, whereas al-Attas emphasizes a substantive reconstruction of values through the integration of science and religion.